Gramsci in the World - Jameson, Fredric; Dainotto, Roberto M. (Roberto Maria), 1962- (Book collections on Project MUSE., 2020)
"GRAMSCI IN THE WORLD demonstrates the ongoing relevance and influence of Antonio Gramsci's Marxist theory on contemporary political struggles, documenting the concrete applications of Gramsci's work around the world. The collection explores some of ways in which Gramsci has been approached by scholars working on different geographies and from different disciplinary perspectives. With pieces ranging from traditional essays to experimental dialogue, the authors challenge both the application and methodology of scholarly engagement with the writings of Gramsci. Co-editors Roberto Dainotto and Fredric Jameson are careful to read Gramsci as part of the current historical moment, rather than affirming a purist version of Gramsci or pitting interpretative camps against one another. The first four essays of the collection explore the textual traces of Gramsci in his notebooks, commenting on his central ideological contributions. For example, Alberto Burgio explores Gramsci's reading of the Paris Commune as a major intervention into our understanding of modernity as a political and cultural structure. Rejecting the idea that modernity marks a new epoch in human history, Burgio argues that Gramsci's differentiation of epoch and duration disallows a critical separation of premodern labor/capital struggle from the modern. The collection then turns to look at the historical limits and possibilities for Gramsci's influence around the world. Harry Harootunian suggests that Gramsci is a major force in pushing Marxist thought outside of a European context, and he sees continuities between Gramsci's The Southern Question and Japanese modernization. Harootunian applies Gramsci's discussion of the improbable alliance between northern industry and southern semi-feudalism in Italy to the Meiji transformation in Japan, focusing particularly on the struggle between the peasantry and new capitalist order. The late Frank Rosengarten maps the importance of Gramsci's writings to Caribbean anti-colonial thinkers like C.L.R. James, Stuart Hall, and Tony Bogues. In her chapter on the Andes, Catherine E. Walsh presents a monologue directed at Gramsci, in which she nuances Gramsci's theories of peasantry and the modern individual with the indigenous epistemology of Abya Yala, which suggests a more communal and interdependent relationship between nature and mankind. Other chapters take up the relevance of Gramsci's work in contemporary India, African American politics, Brazil, the Andes, China, and the Middle East. This collection will be of interest to students and scholars working in critical theory, Marxist theory, political theory, and literary studies"--